2002
DOI: 10.1038/sj.ejcn.1601473
|View full text |Cite
|
Sign up to set email alerts
|

A chart to link child centiles of body mass index, weight and height

Abstract: Background: Weight for height in children is often assessed by comparing the child's weight-for-age centile with their heightfor-age centile. However, this assessment has not been validated statistically, and it differs from the body mass index (BMI) centile. Objective: To study indices of weight-for-height based on weight centile-for-age adjusted for height centile-for-age, and to see how they relate to the BMI centile-for-age. Design: Cross-sectional survey of data for 40 536 boys and girls aged 0 -18 y from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
87
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(91 citation statements)
references
References 12 publications
(13 reference statements)
1
87
0
3
Order By: Relevance
“…Partial correlations were also calculated controlling for the precise time interval between visits. Correlations were calculated separately for children of obese and normal-weight parents, for monozygotic (MZ) and dizygotic (DZ) twins, for first-and second-born twins, for boys and girls and for children age 4 years above or below the 85th percentile of BMI for age and sex relative to 1990 British norms (Cole, 2002), to test for group differences in continuity. Paired samples t-tests were used to compare means of the subscale scores between ages 4 and 11 years.…”
Section: Discussionmentioning
confidence: 99%
“…Partial correlations were also calculated controlling for the precise time interval between visits. Correlations were calculated separately for children of obese and normal-weight parents, for monozygotic (MZ) and dizygotic (DZ) twins, for first-and second-born twins, for boys and girls and for children age 4 years above or below the 85th percentile of BMI for age and sex relative to 1990 British norms (Cole, 2002), to test for group differences in continuity. Paired samples t-tests were used to compare means of the subscale scores between ages 4 and 11 years.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of this method is the assumption that the distribution of a child's weight for age is the same as the distribution of weight at the child's height for age (Himes and Dietz, 1994). In a recent analysis of weight for height indices using a large cross-sectional survey of Dutch individuals, Cole (2002) reported that weight and height centile comparisons similar to ARW, are not an accurate measure of weight-for-height, as the difference between weight and height centiles was poorly correlated to weight and negatively correlated with height. Weight and height centile comparisons similar to ARW risk falsely identifying large numbers of children in need of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to weight and height centile comparisons that assume weight and height are of equal importance, BMI expresses weight adjusted for height (Cole, 2002). In children BMI changes with age and so should be assessed using age-and sex-specific references (Cole et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to be superior to the simpler index WT/height, 19 and is statistically robust because WT is normalised for height by raising height to the power 2 in most age groups. 3,4 In contrast, WT/height remains negatively correlated with height, 19 and is therefore inappropriate. The main limitation of BMI is that is not a direct index of adiposity, and does not reflect individual variability in total or central fatness satisfactorily.…”
Section: Discussionmentioning
confidence: 99%